2021
DOI: 10.1513/annalsats.202004-342oc
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Attainment of Patient-Specific Goals after Endobronchial Valve Treatment

Abstract: Rationale: Bronchoscopic lung volume reduction with endobronchial valves (EBVs) significantly improves clinical outcomes in patients with severe emphysema. However, patientreported outcomes like patient satisfaction and patient-specific treatment goals were never investigated.Objectives: To investigate the patient-satisfaction level 1 year after treatment and patient-specific goals before and 1 year after EBV treatment. Furthermore, the study aimed to investigate whether the level of patient satisfaction or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(24 reference statements)
3
6
0
Order By: Relevance
“…When the presence or magnitude of DH indeed does not identify responders, we would favour the use of outcome measures that are closer to patients' experiences, such as attainment of patient-specific goals, quality of life outcomes and assessment of exercise capacity. 14 In conclusion, the current study demonstrated a significant reduction of DH after EBV treatment. While assessment of DH provides useful insights in the mechanisms of effect of EBV treatment, we propose to prioritize other outcome measures closer to patient experiences after BLVR.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…When the presence or magnitude of DH indeed does not identify responders, we would favour the use of outcome measures that are closer to patients' experiences, such as attainment of patient-specific goals, quality of life outcomes and assessment of exercise capacity. 14 In conclusion, the current study demonstrated a significant reduction of DH after EBV treatment. While assessment of DH provides useful insights in the mechanisms of effect of EBV treatment, we propose to prioritize other outcome measures closer to patient experiences after BLVR.…”
supporting
confidence: 59%
“…When the presence or magnitude of DH indeed does not identify responders, we would favour the use of outcome measures that are closer to patients’ experiences, such as attainment of patient‐specific goals, quality of life outcomes and assessment of exercise capacity 14 …”
mentioning
confidence: 99%
“…In a study conducted in the Netherlands, patient-reported outcomes and goals were investigated 1 year after EBV insertion. 15 Most of the patients (77%) were able to walk, and only 25% of the patients could exercise. COPD patients with giant bullae were excluded from the largest clinical trial of EBV in treatment of COPD.…”
Section: Discussionmentioning
confidence: 97%
“…Patient preference is an important topic of any LVR program, because the treatments performed are often timed in an end-of-life situation of the patient with COPD and often will result in the desired outcome but can also end in disappointment. 19,20 Step 2: Optimal Medical Treatment…”
Section: How Do I Select Patients?mentioning
confidence: 99%
“…Assessment of symptoms and physical limitations is, however, very subjective and also largely dependent on individual patient preferences. 19 It is important to understand and discuss a patient’s treatment outcome expectations and goals and to explain the pros and cons of not performing a treatment or alternative options. Patient preference is an important topic of any LVR program, because the treatments performed are often timed in an end-of-life situation of the patient with COPD and often will result in the desired outcome but can also end in disappointment.…”
Section: How Do I Select Patients?mentioning
confidence: 99%